Implementasi Manajemen Pengajaran PAI Untuk Meningkatkan Prestasi Belajar Siswa Pada SDN Ateuk Kabupaten Aceh Besar - Nurlina Nurlina; Nasir Usman; Sakdiah Ibrahim (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2014)
Teacher’s skillmof organising teaching management is one of the success indicators in implementing Islamic Education at School since good teaching management will really influence students achievement. The object or this reaserch were to find out a program, planning, implementation, and evaluationof Islamic Education teaching result at Elementary School Ateuk Kuta Baro of Aceh Besar. This Reaserch used a descriptive method with a qualitative approach. Data collection technique was carried by an interview, observation, and documentation. The reaserch subject were: teacher of Islamic Education, a principal, vice principal, and students at Elementary School Ateuk of Kuta Baro Aceh Besar. The reaserch result showed that: (1) Teaching plan was designed based on the accepted guidance, (2) Teaching implementation began from an apperception and the continued by a material presentation, (3) Evaluation which was conducted by the teachers with a reference of the Minimum Criteria of Completion was relevant to indicator of graduate competence standars of Islamic Education subject. Evaluation of learning result still used writing ang written tests. Many teachers still had not did yet a learning analysis. Consequently, the quality used was still in doubt. The obstacles faced by Islamic Education teachers in doing an Evaluation of students learning result were: low ability by students and minimum of community’s support. Key words: Teaching Managemenet and Learning Achievment